Evaluation of biodegraded brewers dried grains as a replacement of soybean meal protein in broiler production - sharma, amit (Indian Journal of Animal Nutrition, 2018)
Present study was conducted to assess the effect of replacement of 0, 25, 50 and 75% soybean meal protein with biodegraded brewersâ€™ dried grains on growth performance, carcass yield, biochemical changes and economics of broiler production. Four isocaloric and isonitrogenous dietary treatments contain 22, 20 and 19 % CP and 2800, 2850 and 2950 Kcal/kg ME, during starter (0-2 wks), grower (3-4 wks) and finisher (5-6 wks) phase, respectively. The body weight gain and feeding efficiency (FCR, PER and EER) was similar to control with higher economic return with replacement of 25% soybean meal protein with biodegraded brewerâ€™s dried grains. While carcass and biochemical parameters did not vary with inclusion of biodegraded BDG. Â